SISTEM INFORMASI PENJUALAN E-COMMERCE JASA PERCETAKAN BERBASIS WEB PADA PT TRISTAN ALUR JAYADI - Hansenn Dustin Keane; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
In the era of information technology development, which is becoming increasingly sophisticated every year, there is a printing service company that wants to expand their business using information systems. Therefore, a website is needed as a marketing system and a means of selling printing services to improve service and data processing more effectively and efficiently. The research method used for data collection was by interview, while the system development model used was SDLC Waterfall, which consisted of five stages: requirement definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. As a result, the creation of web-based ordering printing service information system website was successful, using the PHP and MySQL as the main programming languages, while using Visual Studio Code and XAMPP as the main programs. Black box testing was carried out and all modules could be used smoothly according to the expected standard results. User acceptance test (UAT) was also carried out and the result was that the user and several respondents understood the use of website and were successful in carrying out the given test cases.